Exploration of Sialic Acid Diversity and Biology Using Sialoglycan Microarrays. Issue 10 (27th July 2013) - Deng, Lingquan; Chen, Xi; Varki, Ajit; Bush, C. Allen; Bush, C. Allen
ABSTRACT Sialic acids (Sias) are a group of α‐keto acids with a nine‐carbon backbone, which display many types of modifications in nature. The diversity of natural Sia presentations is magnified by a variety of glycosidic linkages to underlying glycans, the sequences and classes of such glycans, as well as the spatial organization of Sias with their surroundings. This diversity is closely linked to the numerous and varied biological functions of Sias. Relatively large libraries of natural and unnatural Sias have recently been chemically/chemoenzymatically synthesized and/or isolated from natural sources. The resulting sialoglycan microarrays have proved to be valuable tools for the exploration of diversity and biology of Sias. Here we provide an overview of Sia diversity in nature, the approaches used to generate sialoglycan microarrays, and the achievements and challenges arising. © 2013 Wiley Periodicals, Inc. Biopolymers 99: 650–665, 2013.